2012
DOI: 10.1073/pnas.1201040109
|View full text |Cite
|
Sign up to set email alerts
|

Integrating ecosystem-service tradeoffs into land-use decisions

Abstract: Recent high-profile efforts have called for integrating ecosystemservice values into important societal decisions, but there are few demonstrations of this approach in practice. We quantified ecosystem-service values to help the largest private landowner in Hawaii, Kamehameha Schools, design a land-use development plan that balances multiple private and public values on its North Shore land holdings (Island of O'ahu) of ∼10,600 ha. We used the InVEST software tool to evaluate the environmental and financial im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
300
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 622 publications
(325 citation statements)
references
References 28 publications
5
300
0
3
Order By: Relevance
“…It showed that such trade-offs varied in different scenarios, suggesting that analyzing trade-offs between ecosystem services did great favor in more effective, efficient, and defensible decision makings (Nelson et al, 2009). Goldstein et al (2012) revealed the trade-offs between carbon storage and water quality and also between environmental improvement and financial returns under seven land-use planning scenarios based on InVEST, which support the implement of the plan for diversified agriculture and forestry management. However, Jackson et al (2013) pointed out that InVEST was widely applied at large scale and with coarse resolution, in comparison, they designed the Polyscape tool, which can be used to disentangle spatially explicit ecosystem services trade-offs to support landscape management, from individual field scale through to catchments scale.…”
Section: Integrated Modeling For Trade-off Analysismentioning
confidence: 99%
“…It showed that such trade-offs varied in different scenarios, suggesting that analyzing trade-offs between ecosystem services did great favor in more effective, efficient, and defensible decision makings (Nelson et al, 2009). Goldstein et al (2012) revealed the trade-offs between carbon storage and water quality and also between environmental improvement and financial returns under seven land-use planning scenarios based on InVEST, which support the implement of the plan for diversified agriculture and forestry management. However, Jackson et al (2013) pointed out that InVEST was widely applied at large scale and with coarse resolution, in comparison, they designed the Polyscape tool, which can be used to disentangle spatially explicit ecosystem services trade-offs to support landscape management, from individual field scale through to catchments scale.…”
Section: Integrated Modeling For Trade-off Analysismentioning
confidence: 99%
“…These HES models are being used to make decisions [e.g., Goldman-Benner et al, 2012;Goldstein et al, 2012;Jackson et al, 2013], but the decision contexts under which they are useful have not been well-described. In addition, the accuracy of the model estimates will influence the land management contexts under which their use is justified.…”
mentioning
confidence: 99%
“…It has been increasingly recognized that human activities aiming to promote certain ESs may lead to negative outcomes for other ESs (Goldstein et al 2012;Maskell et al 2013). The relative gain/loss of the ESs due to management activity also depends on the environmental conditions.…”
Section: Introductionmentioning
confidence: 99%